The effect of textual input versus iconic input in computer assisted instruction on interval recognition - Mong, Bernice Chuey Mei (2004)
This study was initiated out of the growing concern of the prevailing poor sense of pitch intervals among music teacher trainees reflected the unsure perception and direction in their aural training. It was sought that in employing a computer assisted instruction approach in aural training with the use of an aural software will offer music teacher trainees an opportunity to work independently on their aural skills outside the confines of a formal aural lesson in the classroom. This study hopes to bring greater efficiency for music teacher educators to structure aural lessons tailored to music teacher trainees' pace and ability. The objective of the study was to compare the effect of a textual input versus an iconic input in computer assisted instruction on interval recognition of music major and non music major teacher trainees at a teacher's training college. The study also investigated the music teacher trainees' evaluation of the aural training software, Auralia. The textual input group (n=32) and iconic input group (n=32) consisted of music major (n=16) and non music major (n=16) teacher trainees in each input group. The textual input and the iconic input groups completed 20 drill and practice lessons in interval recognition. Both groups completed a progressive test at every session, a total of 20 progressive tests for the 20 lessons. At the end of the treatment in the study, each input group completed a final test from the aural software. Pretest and posttest of the same contents were administered to the groups before and after the study. The results indicated there were no significant differences in interval recognition achievement in the final tests and posttests between the textual input (music major and non music major) and iconic input (music major and non music major) groups. The results also showed no significant differences in music teacher trainees' evaluation of the software between the textual input (music major and non music major) and iconic input (music major and non music major) group. This CAl study suggests that in employing two different inputs, a textual input or an iconic input using aural software had no significant differences on interval recognition.